Rubber composition for fender and fender using same
A rubber composition for fenders with controlled carbon black and crosslinking components addresses the challenge of balancing buckling deformation and manufacturing costs, achieving effective protection and cost-efficiency through enhanced compressibility-reaction force characteristics.
Patent Information
- Application Number
- JP2021046318
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-19
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-03-19
AI Technical Summary
Existing solid-type fender materials face challenges in balancing the need for effective buckling deformation to protect against ship impacts while maintaining a simple three-dimensional shape, as increasing carbon black content for reinforcement leads to higher manufacturing costs and potential buckling issues.
A rubber composition for fenders is formulated with a specific range of carbon black content and crosslinking components, ensuring a maximum loss tangent (tanδ) of 0.48 to 0.8 in a -70°C to +70°C temperature range, using natural rubber and styrene-butadiene rubber (SBR) combinations, to enhance buckling deformation and reduce manufacturing costs.
The composition allows for easy buckling deformation of fender legs, effectively protecting against ship impacts while maintaining a simple shape and reducing production costs, with improved compressibility-reaction force characteristics.
Smart Images

Figure 0007620846000014 
Figure 0007620846000015 
Figure 0007620846000016
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition for a fender to form a fender that is installed, for example, on a quay or the like and absorbs the energy of a ship or the like coming alongside, and to a solid-type fender comprising a cross-linked product of the rubber composition for a fender. [Background technology]
[0002] In solid-type fenders, the support legs, which elastically deform to absorb energy when a ship comes alongside, undergo buckling deformation during the elastic deformation, thereby suppressing excessive increases in reaction force while maintaining the amount of energy absorbed when the ship comes alongside (see Patent Document 1, etc.). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-013120 A [Patent Document 2] JP 2016-151095 A [Patent Document 3] JP 2018-080531 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the case of solid-type fenders, when a ship or other vessel comes alongside, the rubber properties are exerted and the fender undergoes elastic deformation, as described above, and the support legs buckle and deform. This prevents an excessive increase in the reaction force generated in the fender, thereby preventing damage to the ship or vessel, the quay, or the fender itself. In order to make the support leg more susceptible to buckling deformation when coming alongside a ship or the like, the ratio of carbon black used as a reinforcing material to the rubber can be reduced, as can be inferred from the figures showing the compression rate-reaction force characteristics in the examples and comparative examples of Patent Document 1.
[0005] However, since solid-type fenders are huge lumps of rubber and require a large total amount of rubber, the compounded rubber needs to have a low unit price. In terms of manufacturing costs for the fenders, it is generally desirable to increase the proportion of carbon black, which is an inexpensive reinforcing material. However, as is clear from the results of the above figures, if the proportion of carbon black is increased, the support legs become less susceptible to buckling deformation, and the reaction force tends to increase.
[0006] Therefore, in order to make the support legs susceptible to buckling deformation even when the proportion of carbon black is increased, the support legs may be provided with a structure that makes them susceptible to buckling deformation, as described in Patent Document 2, for example. However, the above-mentioned structures often have complex three-dimensional shapes, as shown in, for example, FIG. 1 of Patent Document 2, and thus, in order to put a fender incorporating such a structure into practical use, it is difficult to design it and it is not easy to manufacture, which leads to an increase in the manufacturing costs of the fender.
[0007] It is essential that the support legs maintain a simple three-dimensional shape and contain a large proportion of carbon black to reduce the manufacturing costs of the fender, while still allowing the support legs to easily buckle and deform. The object of the present invention is to provide a rubber composition for a fender which has good rubber properties and can be used to produce a fender, the support legs of which are prone to buckling deformation when a ship or the like comes alongside, more cost-effectively, and a fender using the rubber composition. [Means for solving the problem]
[0008] The present invention comprises rubber, carbon black, and a crosslinking component for crosslinking the rubber, and the crosslinked product has a maximum loss tangent (tan δ) of 0.48 or more in a temperature range of -70°C to +70°C (hereinafter sometimes abbreviated as "specific temperature range"), as determined by the measurement method specified in Japanese Industrial Standard JIS K6394:2007. and the maximum value of the loss tangent is in the range of -70°C to -30°C. A rubber composition for use in a fender.
[0009] The present invention also relates to a fender including a support leg that is elastically deformed when a ship or the like comes alongside, and at least the support leg is made of a crosslinked product of the rubber composition for fenders of the present invention. Effect of the Invention
[0010] According to the present invention, it is possible to provide a rubber composition for fenders which has good rubber properties and enables fenders whose support legs are prone to buckling deformation when moored alongside a ship or the like to be produced more cost-effectively, and a fender using the same. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is an end view showing the appearance of a model of a lambda-type fender produced for measuring the compression ratio-reaction force characteristics in the examples and comparative examples of the present invention. [Diagram 2] FIG. 1(a) is a graph showing the results of measuring the loss tangent (tan δ) in a specific temperature range of the cross-linked product of the rubber composition for fenders of Example 1, and FIG. 1(b) is a graph showing the compression ratio-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for fenders of Example 1. [Diagram 3] FIG. 1(a) is a graph showing the results of measuring the loss tangent (tan δ) in a specific temperature range of the cross-linked product of the rubber composition for fenders of Example 2, and FIG. 1(b) is a graph showing the compression ratio-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for fenders of Example 2. [Figure 4] FIG. 1(a) is a graph showing the results of measuring the loss tangent (tan δ) in a specific temperature range of the cross-linked product of the rubber composition for fenders of Example 3, and FIG. 1(b) is a graph showing the compression ratio-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for fenders of Example 3. [Diagram 5] FIG. 1(a) is a graph showing the results of measuring the loss tangent (tan δ) in a specific temperature range of the cross-linked product of the rubber composition for fenders of Comparative Example 1, and FIG. 1(b) is a graph showing the compression ratio-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for fenders of Comparative Example 1. [Figure 6]FIG. 1(a) is a graph showing the results of measuring the loss tangent (tan δ) in a specific temperature range of the cross-linked product of the rubber composition for fenders of Comparative Example 2, and FIG. 1(b) is a graph showing the compression ratio-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for fenders of Comparative Example 2. [Figure 7] FIG. 1(a) is a graph showing the results of measuring the loss tangent (tan δ) in a specific temperature range of the cross-linked product of the rubber composition for fenders of Comparative Example 3, and FIG. 1(b) is a graph showing the compression ratio-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for fenders of Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] <Rubber composition for fender> As described above, the rubber composition for fenders of the present invention contains rubber, carbon black, and a crosslinking component for crosslinking the rubber, and is characterized in that the maximum value of the loss tangent (tan δ) of the crosslinked product within the above-mentioned specific temperature range, i.e., the temperature range from -70°C to +70°C, is 0.48 or more, as determined by the measurement method specified in Japanese Industrial Standard JIS K6394:2007.
[0013] As explained above, in order to make the support legs of the fender more susceptible to buckling deformation, the ratio of carbon black to rubber can be reduced. However, in that case, the amount of rubber becomes relatively large, which increases the manufacturing costs of the rubber composition for the fender and, ultimately, the fender itself. On the other hand, if the proportion of carbon black is increased in order to reduce manufacturing costs, not only will the rubber properties deteriorate and good compression ratio-reaction force characteristics cannot be obtained, but the support legs will also become less susceptible to buckling deformation.
[0014] Thus, the ratio of carbon black to rubber is the main factor affecting whether or not the support leg is susceptible to buckling deformation. However, according to the inventor's study, in addition to the above-mentioned carbon black ratio, The type of carbon black, or the blend ratio if two or more types of carbon black are used in combination, - Type of rubber, and if two or more types of rubber are used, their mixing ratios, The type, proportion and compounding ratio of crosslinking components for crosslinking rubber, as well as - Types, proportions and mixing ratios of plasticizers and other additives Various factors such as the above also affect how easily or difficultly the support legs are susceptible to buckling deformation.
[0015] The inventors therefore considered a comprehensive evaluation of the susceptibility or resistance of the support legs to buckling deformation, which occurs as a result of the complex interaction of these various factors. As a result, they discovered that it would be sufficient to specify the loss tangent (tan δ) of cross-linked rubber, which is one of the indicators of the viscoelastic properties of rubber, and is measured using the measurement method specified in the Japanese Industrial Standard JIS K6394:2007 "Vulcanized rubber and thermoplastic rubber - Determination of dynamic properties - General guidelines."
[0016] In other words, it was clarified that if the maximum value of the loss tangent (tan δ) of the cross-linked product of the rubber composition for fenders, measured by the above-mentioned measurement method, within the measurement temperature range of -70°C to +70°C (specific temperature range) is 0.48 or more, the support leg made of the rubber composition for fenders can be made more susceptible to buckling deformation. In other words, if the maximum value of the loss tangent (tan δ) within the above-mentioned specific temperature range is set to the above-mentioned range, the support leg can maintain a simple three-dimensional shape and the proportion of carbon black can be increased to reduce the manufacturing costs of the fender, while still making the support leg more susceptible to buckling deformation.
[0017] Furthermore, it is possible to suppress an excessive increase in the reaction force generated in the fender when a ship or the like comes alongside, thereby preventing damage to the ship or the quay, or the fender itself. These facts are also evident from the results of the examples and comparative examples described below. Although there is no particular limitation on the upper limit of the maximum value of the loss tangent (tan δ) within the above-mentioned specific temperature range, in consideration of maintaining good compressibility-reaction force characteristics of the fender, it is preferable that the maximum value of the loss tangent (tan δ) within the above-mentioned range be 0.8 or less, and particularly 0.6 or less.
[0018] The method for measuring the loss tangent (tan δ) of the crosslinked product of the rubber composition for fenders in a specific temperature range based on the above-mentioned JIS standard is as follows. <Loss tangent measurement method> The rubber composition for a fender for which the loss tangent (tan δ) is to be measured is press-crosslinked at 140°C for 60 minutes to produce a crosslinked sheet having a thickness of 2 mm. The crosslinked sheet is then punched out to prepare a rectangular test piece as specified in JIS K6394:2007.
[0019] Next, using a small-scale testing device specified in the standard, the loss tangent (tan δ) is measured in a specific temperature range of -70°C to +70°C using the tensile method of the forced vibration resonance method, and the maximum loss tangent (tan δ) in that specific temperature range is determined from the measurement results. Incidentally, Patent Document 1 describes that the loss tangent (tan δ) at 23° C. is preferably less than 0.11 or less than 0.14 depending on the rate of elasticity change.
[0020] Furthermore, Patent Document 3 describes that the loss tangent (tan δ) at 23° C. is preferably less than 0.10. However, the preferred range in any of these descriptions does not overlap at all with the range of 0.48 or more specified in the present invention, and there is no mention of the relationship between the loss tangent (tan δ) and the ease or resistance to buckling deformation.
[0021] Carbon Black As the carbon black, various carbon blacks capable of functioning as a rubber filler (filling agent, reinforcing agent), such as furnace black, acetylene black, and ketjen black, can be used. Specific examples of carbon black include, but are not limited to, the following carbon blacks:
[0022] From the SEAT (registered trademark) series manufactured by Tokai Carbon Co., Ltd., SEAT 9H (SAF-HS, nitrogen adsorption specific surface area: 142 m 2 / g], SEAT 9 [SAF, nitrogen adsorption specific surface area: 142 m 2 / g], SEAT 7HM [N234, nitrogen adsorption specific surface area: 126 m 2 / g], Seast 6 [ISAF, nitrogen adsorption specific surface area: 119 m 2 / g], SEAT 600 [ISAF-LS, nitrogen adsorption specific surface area: 106 m 2 / g], SEAT 5H [IISAF, nitrogen adsorption specific surface area: 99 m 2 / g], Seest KH [N399, nitrogen adsorption specific surface area: 93 m 2 / g], SEAT 3H [HAF-HS, nitrogen adsorption specific surface area: 82 m 2 / g], SEAT NH [N351, nitrogen adsorption specific surface area: 74 m 2 / g], SEAT 3 [HAF, nitrogen adsorption specific surface area: 79 m 2 / g], SEAT N [LI-HAF, nitrogen adsorption specific surface area: 74 m 2 / g], SEAT 300 [HAF-LS, nitrogen adsorption specific surface area: 84 m 2 / g], SEAT 116HM [MAF-HS, nitrogen adsorption specific surface area: 56 m 2 / g], SEAT 116 [MAF, nitrogen adsorption specific surface area: 49 m 2 / g], seast SO〔FEF, nitrogen adsorption specific surface area: 42m 2 / g], Seast V [GPF, nitrogen adsorption specific surface area: 27m 2 / g], SEAT SVH [SRF-HS, nitrogen adsorption specific surface area: 32 m 2 / g], Seest FY [SRF-HS, nitrogen adsorption specific surface area: 29 m 2 / g], SEAT S [SRF, nitrogen adsorption specific surface area: 27 m 2 / g], SEAT SP [SRF-LS, nitrogen adsorption specific surface area: 23 m 2 / g], SEAT TA [FT class, nitrogen adsorption specific surface area: 19m 2 / g]
[0023] Asahi #95 (nitrogen adsorption specific surface area: 147 m) manufactured by Asahi Carbon Co., Ltd. 2 / g], Asahi #80 [ISAF, nitrogen adsorption specific surface area: 115 m 2 / g], Asahi #70 [HAF, nitrogen adsorption specific surface area: 77 m 2 / g], Asahi #70L [Nitrogen adsorption specific surface area: 84 m 2 / g], Asahi AX-015 [Nitrogen adsorption specific surface area: 145 m 2 / g], Asahi F-200GS [Nitrogen adsorption specific surface area: 51 m 2 / g], Asahi #65 [Nitrogen adsorption specific surface area: 42 m 2 / g], Asahi #60HN [Nitrogen adsorption specific surface area: 48 m 2 / g], Asahi #60U [Nitrogen adsorption specific surface area: 43 m 2 / g], Asahi #55 [Nitrogen adsorption specific surface area: 26 m 2 / g], Asahi #50HG [Nitrogen adsorption specific surface area: 20m 2 / g], Asahi #52 [Nitrogen adsorption specific surface area: 28 m 2 / g], Asahi #51 [Nitrogen adsorption specific surface area: 20 m 2 / g], Asahi #50U [Nitrogen adsorption specific surface area: 27 m 2 / g], Asahi #50 [Nitrogen adsorption specific surface area: 23 m 2 / g], Asahi #35 [Nitrogen adsorption specific surface area: 24 m 2 / g], Asahi #22K [Nitrogen adsorption specific surface area: 21 m 2 / g], Asahi #15HS [Nitrogen adsorption specific surface area: 14 m 2 / g], Asahi #15 [Nitrogen adsorption specific surface area: 12 m 2 / g], Asahi #8 [Nitrogen adsorption specific surface area: 12 m 2 / g], Asahi Thermal [Nitrogen adsorption specific surface area: 24 m 2 / g]
[0024] One or more of these carbon blacks can be used. In particular, as the carbon black, it is preferable to use furnace black such as SAF, ISAF, HAF, MAF, FEF, GPF, or SRF. <Carbon black ratio> The proportion of carbon black is preferably 65 parts by mass or more and 80 parts by mass or less per 100 parts by mass of the total amount of rubber.
[0025] If the proportion of carbon black is less than this range, the proportion of rubber will be relatively high, resulting in increased production costs for the rubber composition for the fender and, ultimately, for the fender. In contrast, by setting the proportion of carbon black to the above range or more, the amount of rubber can be relatively reduced, thereby reducing the production costs of the rubber composition for a fender and, ultimately, the fender.
[0026] On the other hand, if the proportion of carbon black exceeds the above range, the reinforcing properties of the rubber due to the carbon black will be too strong, and the cross-linked product itself will become too hard. Furthermore, the maximum value of the loss tangent (tan δ) within a specific temperature range will become smaller, making it difficult for the support legs to buckle. Furthermore, the viscosity of the rubber composition for a fender before crosslinking may increase, resulting in reduced processability.
[0027] Furthermore, it may become difficult to knead the various components to prepare the rubber composition for the fender, or to knead the rubber composition for the fender or mold it into any three-dimensional shape to manufacture the fender. In contrast, by setting the proportion of carbon black within the above range, the reinforcing properties of the rubber can be prevented from becoming too strong, and the maximum value of the loss tangent (tan δ) within a specific temperature range can be prevented from decreasing, making it easier for the support legs to buckle.
[0028] In addition, it is also possible to suppress a decrease in the processability of the rubber composition for a fender. When two or more types of carbon black are used in combination, the total proportion of the carbon blacks should be within the range of 65 parts by mass or more and 80 parts by mass or less per 100 parts by mass of the total amount of rubber. When two or more types of carbon black are used in combination, for example, a carbon black having a large nitrogen adsorption specific surface area and a strong reinforcing effect on rubber may be used in combination with a carbon black having a small nitrogen adsorption specific surface area and a weaker reinforcing effect.
[0029] In this case, the overall proportion of carbon black can be maintained, and the increase in the manufacturing cost of the fender can be suppressed, while the reinforcing properties of the rubber can be weakened and the maximum value of the loss tangent (tan δ) in a specific temperature range can be further increased. In addition, the support leg can be made even more susceptible to buckling deformation, and the deterioration of the processability of the rubber composition for a fender can be more effectively suppressed.
[0030] <Rubber> As the rubber, various types of crosslinkable rubber can be used, and in particular, natural rubber is preferably used in order to impart good compression ratio-reaction force characteristics to the fender. Examples of natural rubber include various grades of natural rubber such as TSR-20 and RSS#3, and also deproteinized natural rubber can be used.
[0031] One or more of these natural rubbers can be used. As the rubber, natural rubber may be used alone (including a combination of two or more kinds of natural rubber), or natural rubber may be used in combination with another rubber. Examples of other rubbers include styrene butadiene rubber (SBR), butadiene rubber (BR), isoprene rubber (IR), butyl rubber (IIR), ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), chlorosulfonated polyethylene (CSM), acrylonitrile butadiene rubber (NBR), hydrogenated acrylonitrile butadiene rubber (HNBR), acrylic rubber (ACM), fluororubber (FKM), epichlorohydrin rubber, and the like.
[0032] One or more of these synthetic rubbers can be used. In addition, in consideration of further increasing the maximum value of the loss tangent (tan δ) in a specific temperature range and appropriately balancing the rubber properties of the cross-linked product to impart good compression ratio-reaction force characteristics to the fender, SBR and / or BR are preferred as the other rubber. (SBR) SBR includes oil-extended types in which flexibility is adjusted by adding extender oil, and non-oil-extended types in which no extender oil is added. Either type of SBR can be used in the present invention.
[0033] Examples of non-oil-extended SBR include, but are not limited to, JSR (registered trademark) 1500 (bound styrene content: 23.5%), JSR1502 (bound styrene content: 23.5%), JSR1503 (bound styrene content: 23.5%), and JSR1507 (bound styrene content: 23.5%), all manufactured by JSR Corporation. Examples of oil-extended SBR include, but are not limited to, JSR1732 (bound styrene content: 23.5%, oil content: 27.3%), JSR0122 (bound styrene content: 37%, oil content: 25.4%), JSR1778 (bound styrene content: 23.5%, oil content: 27.3%), and JSR1778N (bound styrene content: 23.5%, oil content: 27.3%), all of which are manufactured by JSR Corporation.
[0034] One or more of these non-oil-extended and / or oil-extended SBRs can be used. When natural rubber and SBR are used in combination, the amount of natural rubber is preferably at least 65 parts by mass, particularly preferably at least 70 parts by mass, and is preferably at most 85 parts by mass, particularly preferably at most 75 parts by mass, per 100 parts by mass of the total amount of rubber.
[0035] If the SBR content is less than this range, the effects of further increasing the maximum loss tangent (tan δ) within a specific temperature range or imparting good compression rate-reaction force characteristics to the fender may not be fully obtained. Furthermore, the abrasion resistance may decrease, making the fender more susceptible to wear when repeatedly used alongside ships, etc., and the durability of the fender may become insufficient.
[0036] On the other hand, if the SBR content is higher than the above range, the tear strength will be lower and, for example, if the fender has minute scratches, it may be more susceptible to cracks when it is used repeatedly alongside ships, etc. In contrast, by setting the proportion of SBR within the above range, the effect of using the SBR in combination can be further improved.
[0037] When oil-extended SBR is used, the SBR percentage refers to the percentage of SBR itself as solids (rubber) contained in the oil-extended SBR. (BR) As the BR, any of various BRs having a polybutadiene structure in the molecule and having crosslinking properties can be used.
[0038] In particular, high-cis BR having a cis-1,4 bond content of 95% or more is preferred, since it exhibits little change in physical properties due to temperature and has stable compression modulus-reaction force characteristics. In addition, there are two types of BR: oil-extended, in which flexibility is adjusted by adding an extender oil, and non-oil-extended, in which no extender oil is added. Either type of BR can be used in the present invention. As specific examples of the non-oil-extended high-cis BR, for example, one or more of the following various BRs can be used.
[0039] UBEPOL (registered trademark) BR150 (cis-1,4 bond content: 98% by mass), BR130B (cis-1,4 bond content: 96% by mass), BR150B (cis-1,4 bond content: 97% by mass), BR360B (cis-1,4 bond content: 98% by mass), BR150L (cis-1,4 bond content: 98% by mass), BR360L (cis-1,4 bond content: 98% by mass), BR230 (cis-1,4 bond content: 98% by mass), and BR710 (cis-1,4 bond content: 98% by mass), manufactured by Ube Industries, Ltd.
[0040] A specific example of the oil-extended high-cis BR is UBEPOL BR133P (cis-1,4 bond content: 98 mass %, oil amount: 37.5 phr) manufactured by Ube Industries, Ltd. One or more of these non-oil-extended and / or oil-extended BRs can be used.
[0041] When natural rubber and BR are used in combination, the proportion of the natural rubber is preferably 65 parts by mass or more, particularly 70 parts by mass or more, and 85 parts by mass or less, particularly 75 parts by mass or less, per 100 parts by mass of the total amount of rubber. When oil-extended BR is used, the BR percentage refers to the percentage of BR itself as solid content (rubber) contained in the oil-extended BR.
[0042] <Crosslinking component> Examples of the crosslinking component for crosslinking the rubber include a crosslinking agent and a crosslinking accelerator. (Crosslinking agent) Examples of the crosslinking agent include sulfur-based crosslinking agents and peroxide-based crosslinking agents, with sulfur-based crosslinking agents being particularly preferred.
[0043] Examples of the sulfur-based crosslinking agent include powdered sulfur, powdered sulfur in oil, precipitated sulfur, colloidal sulfur, dispersible sulfur, and other sulfur-containing organic compounds such as tetramethylthiuram disulfide and N,N-dithiobismorpholine, with sulfur being particularly preferred. The proportion of sulfur is preferably 1.2 parts by mass or more and 3 parts by mass or less per 100 parts by mass of the total amount of rubber.
[0044] If the proportion of sulfur is below this range, the maximum value of the loss tangent (tan δ) in a specific temperature range becomes small, and the support legs may become less susceptible to buckling deformation. Furthermore, the crosslinking rate of the rubber composition for a fender as a whole becomes slow, and the time required for crosslinking becomes long, which may result in a decrease in productivity of the fender. Furthermore, if the proportion of sulfur exceeds the above range, the compression set after crosslinking may become large, or the excess sulfur may bloom on the surface of the fender.
[0045] When using, for example, powdered sulfur in oil, dispersible sulfur, or the like, the above ratio refers to the ratio of sulfur itself as an active ingredient contained therein. When an organic sulfur-containing compound is used as the crosslinking agent, the proportion thereof is preferably adjusted so that the proportion of sulfur contained in the molecule per 100 parts by mass of the total amount of rubber falls within the above range.
[0046] (Crosslinking accelerator) Examples of the crosslinking accelerator include inorganic accelerators such as slaked lime, magnesia (MgO), litharge (PbO), etc., and the following various organic accelerators, which may be used alone or in combination. Guanidine accelerators such as 1,3-di-o-tolylguanidine, 1,3-diphenylguanidine, 1-o-tolylbiguanide, and di-o-tolylguanidine salts of dicatechol borate.
[0047] Thiazole accelerators such as 2-mercaptobenzothiazole and di-2-benzothiazolyl disulfide. Sulfenamide accelerators such as N-tert-butyl-2-benzothiazolylsulfenamide and N-cyclohexyl-2-benzothiazolylsulfenamide. Thiuram accelerators such as tetramethylthiuram monosulfide, tetramethylthiuram disulfide, tetraethylthiuram disulfide, and dipentamethylenethiuram tetrasulfide.
[0048] Dithiocarbamate accelerators such as zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, and zinc dibutyldithiocarbamate. Thiourea accelerators such as N,N'-diphenylthiourea, trimethylthiourea, and N,N'-diethylthiourea. The proportion of the crosslinking accelerator can be set arbitrarily depending on the type, but in general, it is preferably 0.5 parts by mass or more and 5 parts by mass or less individually per 100 parts by mass of the total amount of rubber.
[0049] <others> The rubber composition for fenders may further contain fillers other than carbon black, antioxidants, crosslinking assistants, plasticizers, waxes, colorants, tackifiers, etc. in any proportion, as required. (Other fillers) Examples of fillers other than carbon black include silica.
[0050] (Anti-aging agent) The antioxidant may be one or more of various antioxidants classified according to their main functions, such as weather-resistant antioxidants and heat-resistant antioxidants. Examples of the antioxidant include N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine and 2,2,4-trimethyl-1,2-dihydroquinoline polymers.
[0051] In particular, N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine is preferred because of its excellent effect of preventing sunlight cracking, ozone cracking, and flex cracking. The proportion of the antioxidant is preferably 0.5 parts by mass or more and 7 parts by mass or less per 100 parts by mass of the total amount of rubber. (Crosslinking aid) Examples of the crosslinking aid include one or more of metal compounds such as zinc oxide; fatty acids such as stearic acid, oleic acid, cottonseed fatty acid, and other conventionally known crosslinking aids.
[0052] The proportion of each crosslinking aid is preferably at least 0.5 parts by mass and at most 7 parts by mass per 100 parts by mass of the total amount of rubber. (Plasticizer) The plasticizer may be, for example, oil or liquid rubber. Among these, the oil may be, but is not limited to, one or more of various grades of oil such as Diana (registered trademark) process oil PW, NH, NP, NS, NR, NM, AC, and AH manufactured by Idemitsu Kosan Co., Ltd.
[0053] Examples of the liquid rubber include one or more of liquid isoprene rubber, hydrogenated liquid isoprene rubber, liquid butadiene rubber, liquid styrene butadiene rubber, and end-modified products thereof. The proportion of the plasticizer is preferably at least 1 part by mass, particularly preferably at least 3 parts by mass, and is preferably at most 30 parts by mass, particularly preferably at most 13 parts by mass, per 100 parts by mass of the total amount of rubber.
[0054] (wax) Examples of waxes include, but are not limited to, OZOACE (registered trademark) 0355 manufactured by Nippon Seiro Co., Ltd., and SANNOC (registered trademark), SANNOC N, and SANNOC P manufactured by Ouchi Shinko Chemical Industry Co., Ltd. These waxes function in combination with antioxidants to prevent sun cracking and ozone cracking.
[0055] The proportion of the wax is preferably at least 0.5 parts by mass and at most 5 parts by mass per 100 parts by mass of the total amount of rubber. The rubber composition for fenders can be prepared, for example, by first kneading the above-mentioned components other than the crosslinking component using a kneader, Banbury mixer or the like, and then adding and kneading the crosslinking component.
[0056] The process for producing a fender using the prepared rubber composition for fenders may be the same as in the conventional process. That is, the fender can be produced by combining any steps such as molding, sheet molding, assembly, and crosslinking depending on the size and shape of the fender to be produced. 《Fender》 The fender of the present invention includes a support leg that is fixed to a quay or the like and elastically deforms when a ship or the like comes alongside, and is characterized in that at least the support leg is made of a cross-linked product of the rubber composition for fenders of the present invention.
[0057] Specific examples of the fender of the present invention include the following various fenders. An arch-shaped fender (including so-called inverted V-shaped, lambda (λ)-shaped and beta (β)-shaped) in which a head portion that constitutes the flat impact surface against which a ship or the like comes alongside, and a pair of support legs that hang down while spreading out in the fore-and-aft direction from the head portion are integrally formed from a cross-linked product of a rubber composition for fenders. A so-called kappa (κ) type fender in which a disk-shaped head and a truncated cone-shaped support leg that hangs down while expanding radially from the head are integrally formed by a cross-linked product of a rubber composition for fenders. A so-called π-type fender comprising a head portion made of steel or the like and a pair of support legs made of a cross-linked product of a rubber composition for fenders that hang down from the head portion while spreading out in the front-to-rear direction.
[0058] In any of these fenders, by forming at least the support legs from the crosslinked product of the rubber composition for fenders of the present invention described above, it is possible to make the fenders more susceptible to buckling deformation when coming alongside a ship or the like. Moreover, the proportion of rubber can be reduced, thereby reducing the manufacturing costs of the fender. In particular, the effect of reducing manufacturing costs is remarkable in arch-type or kappa-type fenders in which the entire fender, including not only the support legs but also the head portion, is integrally formed from the crosslinked product of the rubber composition for fenders of the present invention. EXAMPLES
[0059] The present invention will be further described below based on examples and comparative examples, but the configuration of the present invention is not necessarily limited to these examples. Example 1 (Preparation of Rubber Composition for Fender) The rubber used was a combination of 70 parts by mass of natural rubber (TSR20 product) and 30 parts by mass of non-oil extended SBR (JSR1502 manufactured by JSR Corporation, previously mentioned, bound styrene content: 23.5%).
[0060] A total of 100 parts by mass of both rubbers was kneaded together with the components shown in Table 1 below using a 3 L kneader.
[0061] [Table 1]
[0062] The components in Table 1 are as follows. The parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. Carbon black (i): GPF, the aforementioned Tokai Carbon Co., Ltd.'s Seast V, nitrogen adsorption specific surface area: 27 m 2 / g Carbon black (ii): HAF, the aforementioned Tokai Carbon Co., Ltd.'s Seast 3, nitrogen adsorption specific surface area: 79 m 2 / g Crosslinking aid I: Zinc oxide type 2, manufactured by Mitsui Mining & Smelting Co., Ltd. Crosslinking aid II: stearic acid, trade name Tsubaki manufactured by NOF Corporation Antioxidant: N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine, Nocrac (registered trademark) 6C manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Wax: Sannock, manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Oil: Diana Process Oil NH-70S manufactured by Idemitsu Kosan Co., Ltd. Next, the crosslinking components shown in Table 2 below were added, and the mixture was further kneaded using an open roll to prepare a rubber composition for a fender.
[0063] [Table 2]
[0064] The components in Table 2 are as follows. The parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. Crosslinking agent: Kinkajirushi 5% oil-filled fine sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Accelerator NS: N-tert-butyl-2-benzothiazolyl sulfenamide, a sulfenamide-based accelerator, Noccela (registered trademark) NS manufactured by Ouchi Shinko Chemical Industry Co., Ltd. The proportion of SBR was 30 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black in total was 75 parts by mass per 100 parts by mass of the total amount of rubber.
[0065] Example 2 (Preparation of Rubber Composition for Fender) The rubber used was a combination of 70 parts by mass of natural rubber (TSR20 product) and 30 parts by mass of non-oil extended SBR (JSR1502 manufactured by JSR Corporation, previously mentioned, bound styrene content: 23.5%).
[0066] A total of 100 parts by mass of both rubbers was kneaded together with the components shown in Table 3 below using a 3 L kneader.
[0067] [Table 3]
[0068] The components in Table 3 are the same as those in Example 1. Furthermore, the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. Next, the crosslinking components shown in Table 4 below were added, and further kneaded using an open roll to prepare a rubber composition for a fender.
[0069] [Table 4]
[0070] The components in Table 4 are the same as those in Example 1. Furthermore, the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. The proportion of SBR was 30 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black in total was 65 parts by mass per 100 parts by mass of the total amount of rubber. Example 3 (Preparation of Rubber Composition for Fender) The rubber used was a combination of 70 parts by mass of natural rubber (TSR20 product) and 30 parts by mass of non-oil extended SBR (JSR1502 manufactured by JSR Corporation, previously mentioned, bound styrene content: 23.5%).
[0071] A total of 100 parts by mass of both rubbers was kneaded together with the components shown in Table 5 below using a 3 L kneader.
[0072] [Table 5]
[0073] The components in Table 5 are the same as those in Example 1. Furthermore, the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. Next, the crosslinking components shown in Table 6 below were added, and further kneaded using an open roll to prepare a rubber composition for a fender.
[0074] [Table 6]
[0075] The components in Table 6 are the same as those in Example 1. Furthermore, the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. The proportion of SBR was 30 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of carbon black (ii) was 65 parts by mass per 100 parts by mass of the total amount of rubber. Comparative Example 1 (Preparation of Rubber Composition for Fender) The rubber used was a combination of 70 parts by mass of natural rubber (TSR20 product) and 30 parts by mass of non-oil extended SBR (JSR1502 manufactured by JSR Corporation, previously mentioned, bound styrene content: 23.5%).
[0076] A total of 100 parts by mass of both rubbers was kneaded together with the components shown in Table 7 below using a 3 L kneader.
[0077] [Table 7]
[0078] The components in Table 7 are the same as those in Example 1. Furthermore, the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. Next, the crosslinking components shown in Table 8 below were added, and the mixture was further kneaded using an open roll to prepare a rubber composition for a fender.
[0079] [Table 8]
[0080] The components in Table 8 are the same as those in Example 1. Furthermore, the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. The proportion of SBR was 30 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black in total was 83 parts by mass per 100 parts by mass of the total amount of rubber. Comparative Example 2 (Preparation of Rubber Composition for Fender) The rubber used was a combination of 70 parts by mass of natural rubber (TSR20 product) and 30 parts by mass of non-oil extended SBR (JSR1502 manufactured by JSR Corporation, previously mentioned, bound styrene content: 23.5%).
[0081] A total of 100 parts by mass of both rubbers was kneaded together with the components shown in Table 9 below using a 3 L kneader.
[0082] [Table 9]
[0083] Carbon black (iii) in Table 9 is the above-mentioned SEAST 6 (ISAF, nitrogen adsorption specific surface area: 119 m) manufactured by Tokai Carbon Co., Ltd. 2 / g), and the other components are the same as in Example 1. Furthermore, the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. Next, the crosslinking components shown in Table 10 below were added, and the mixture was further kneaded using an open roll to prepare a rubber composition for a fender.
[0084] [Table 10]
[0085] The components in Table 10 are the same as those in Example 1. Furthermore, the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. The proportion of SBR was 30 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of carbon black (iii) was 75 parts by mass per 100 parts by mass of the total amount of rubber. Comparative Example 3 (Preparation of Rubber Composition for Fender) The rubber used was a combination of 80 parts by mass of natural rubber (TSR20 product) and 20 parts by mass of non-oil-extended SBR (JSR1502 manufactured by JSR Corporation, previously mentioned, bound styrene content: 23.5%).
[0086] A total of 100 parts by mass of both rubbers was kneaded together with the components shown in Table 11 below using a 3 L kneader.
[0087] [Table 11]
[0088] The components in Table 11 are the same as those in Example 1. Furthermore, the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. Next, the crosslinking components shown in Table 12 below were added, and the mixture was further kneaded using an open roll to prepare a rubber composition for a fender.
[0089] [Table 12]
[0090] The components in Table 12 are the same as those in Example 1. Furthermore, the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. The proportion of SBR was 20 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of carbon black (ii) was 70 parts by mass per 100 parts by mass of the total amount of rubber. <Loss tangent measurement> The rubber compositions for fenders prepared in each of the Examples and Comparative Examples were press-crosslinked at 140°C for 60 minutes to produce crosslinked sheets having a thickness of 2 mm. The crosslinked sheets were punched out to produce rectangular test pieces as specified in JIS K6394:2007.
[0091] The loss tangent (tan δ) of the produced rectangular test piece was measured in a specific temperature range of −70° C. to +70° C. in accordance with the measurement method described above. The results of Example 1 are shown in FIG. 2(a), the results of Example 2 in FIG. 3(a), the results of Example 3 in FIG. 4(a), the results of Comparative Example 1 in FIG. 5(a), the results of Comparative Example 2 in FIG. 6(a), and the results of Comparative Example 3 in FIG. 7(a). From each of the figures, the maximum value of the loss tangent (tan δ) in the specific temperature range was obtained for each of the examples and comparative examples, and the maximum value of 0.48 or more was evaluated as "○", and the maximum value less than 0.48 was evaluated as "×".
[0092] <Type A durometer hardness measurement> The rubber compositions for fenders prepared in each of the Examples and Comparative Examples were press-crosslinked at 140° C. for 60 minutes to prepare crosslinked sheets having a thickness of 2 mm. Next, three of the crosslinked sheets were stacked together to form a test piece for hardness measurement, and the type A durometer hardness was measured in accordance with the measurement method specified in Japanese Industrial Standard JIS K6253-3:2012 "Vulcanized rubber and thermoplastic rubber - Determination of hardness - Part 3: Durometer hardness."
[0093] The measurement temperature was the standard test temperature (23°C). Tensile Test The rubber compositions for fenders prepared in each of the Examples and Comparative Examples were press-crosslinked at 140° C. for 60 minutes to prepare crosslinked sheets having a thickness of 3 mm. Next, the crosslinked sheet was punched out to prepare dumbbell-shaped No. 3 test pieces as specified in the Japanese Industrial Standard JIS K6251:2017 "Vulcanized rubber and thermoplastic rubber - Determination of tensile properties".
[0094] The test pieces thus prepared were subjected to a tensile test as specified in the same standard to determine the tensile strength TS (MPa) and the elongation at break Eb (%). The measurement temperature was the standard test temperature (23°C). The tensile strength TS was evaluated as follows: less than 16 MPa was evaluated as "x", 16 MPa or more but less than 20 MPa was evaluated as "○", and 20 MPa or more was evaluated as "◎".
[0095] The elongation at break Eb was evaluated as follows: less than 350% was evaluated as "x", 350% or more but less than 400% was evaluated as "◯", and 400% or more was evaluated as "◎". <Making a model of a fender> Using the rubber compositions for fenders prepared in each of the Examples and Comparative Examples, a miniature-sized model 1 of a lambda-type fender having an end face shape shown in FIG. 1 was produced.
[0096] That is, a head 3 constituting a planar impact surface 2, a pair of support legs 4 hanging down from the head 3 while spreading out in the fore-and-aft direction, and a mounting flange 5 connected to the lower ends of the support legs 4 and protruding outward were integrally formed from a rubber composition for fenders and cross-linked to produce model 1. The crosslinking conditions were 140°C x 120 minutes.
[0097] The dimensions of each part were as follows: width W1 of head 3 was 65 mm, height H was 100 mm, width W2 between the tips of flange parts 5 was 180 mm, and total length was 200 mm. <Compression rate-reaction force characteristic test> The fender model 1 created above was compressed three times in the height direction at a speed of 15 mm / min at the standard test temperature (23°C) with a maximum compression of 52.5% of the height H, with a 3-minute interval between each compression.
[0098] The average value of the reaction force according to the compression ratio during the second and third compressions was then calculated, and the compression ratio-reaction force characteristics were calculated by plotting the compression ratio (%) on the horizontal axis and the reaction force (kN) on the vertical axis. The results of Example 1 are shown in FIG. 2(b), the results of Example 2 in FIG. 3(b), the results of Example 3 in FIG. 4(b), the results of Comparative Example 1 in FIG. 5(b), the results of Comparative Example 2 in FIG. 6(b), and the results of Comparative Example 3 in FIG. 7(b). As shown in Figures 5(b) to 7(b), it was found that none of the fenders made of the rubber compositions for fenders in Comparative Examples 1 to 3 buckled when compressed, and the reaction force unilaterally increased depending on the compression rate.
[0099] Therefore, Comparative Examples 1 to 3 were evaluated as "x" because there was no buckling deformation. On the other hand, although the fenders made of the rubber compositions for fenders in Examples 1 to 3 all had the same shape as those in Comparative Examples 1 to 3, as can be seen in Figures 2(b) to 4(b), the reaction force decreased after the intermediate reaction force value RR, indicating that buckling deformation occurred due to compression. Therefore, Examples 1 to 3 were rated as "good" because buckling deformation occurred.
[0100] The above results are shown in Table 13.
[0101] [Table 13]
[0102] From the results of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 13, it was found that by forming at least the support leg of the fender from a rubber composition for fenders having a loss tangent (tan δ) of the cross-linked product of 0.48 or more in a specific temperature range, it is possible to make the support leg more susceptible to buckling deformation while reducing manufacturing costs. However, it has been found that in order to achieve this, the proportion of carbon black is preferably 65 to 80 parts by mass per 100 parts by mass of the total amount of rubber.
[0103] Furthermore, in a system in which natural rubber and SBR are used in combination as the rubber, it has been found that the proportion of natural rubber is preferably 65 parts by mass or more, and particularly preferably 70 parts by mass or more, per 100 parts by mass of the total amount of rubber, and is preferably 85 parts by mass or less, and particularly preferably 75 parts by mass or less. Furthermore, it was found that the ratio of sulfur as a crosslinking agent in the crosslinking components is preferably 1.2 parts by mass or more and 3 parts by mass or less per 100 parts by mass of the total amount of rubber. [Explanation of symbols]
[0104] 1 Fender model 2 Impact surface 3 head 4 Support legs 5 Flange
Claims
1. The crosslinked product contains rubber, carbon black, and a crosslinking component for crosslinking the rubber, and the maximum loss tangent of the crosslinked product in the temperature range of −70° C. to +70° C. is 0.48 or more, as determined by the measurement method specified in Japanese Industrial Standard JIS K6394:2007; The rubber composition for a fender has a maximum value of the loss tangent in the range of -70°C to -30°C.
2. 2. The rubber composition for a fender according to claim 1, wherein the proportion of the carbon black is 65 parts by mass or more and 80 parts by mass or less per 100 parts by mass of the total amount of the rubber.
3. The rubber composition for a fender according to claim 1 or 2, wherein the rubber contains at least natural rubber.
4. A fender comprising a support leg that is elastically deformed when a ship or the like comes alongside, at least the support leg being made of a crosslinked product of the rubber composition for fenders according to any one of claims 1 to 3.
5. The fender is the one described in claim 4, which has a head portion constituting a planar impact surface and a pair of support legs hanging down while expanding in the fore-and-aft direction from the head portion, which are formed into an arch shape by the rubber composition for the fender.
Citation Information
Patent Citations
set it is protection device
JP1984183914U
Rubber composition
JP1989043544A
Fender
JP2002013120A
Fender
JP2016151095A
Rubber composition for fender
JP2018080531A